Implementasi Sistem Monitoring Running Hour dan Temperature pada Alat Berat Vibro HAMM dengan Teknologi IoT - Istiyono, Yogi Priyo; Firasanto, Gaguk (EPIC Journal of Electrical Power Instrumentation and Control, 2024)
Maintenance or commonly referred to as maintenance is a function of activities in a company that is as important as the functions of other activities. It becomes interesting if every use of an equipment can be known how long it has been used.In this study, running hours were measured using an microcontroller, an I2C (Inter Integrated Circuit) interface with RTC (Real Time Clock) DS1307 as a source of time information and a DS18B20 temperature sensor. The measurement data is displayed with a 20×4 LCD (Liquid Crystal Display) module, the Thingspeak web server and an android application that is connected to the GSM900A module.This tool has been tested and can work on heavy equipment such as vibro HAMM. The data displayed in the form of information on working temperature, date, working hours of the tool as well as notification alerts when the working temperature exceeds a predetermined limit.